Teacher Perceptions Toward Closing the Procedural Knowledge Gap among Teachers in Implementing Smart Learning - et. al., Dr. Alexandria Proff, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research objective was to discern teachers' competence in implementing smart learning tools, identify any present gaps, and make recommendations toward closing the procedural knowledge gap among teachers. This study employed a mixed-method approach that utilized quantitative and qualitative data collection and analysis, utilizing three tools: questionnaires, semi-structured interviews, and school-related documentation. A total of 63 male teachers participated in an online, four-point, forced-choice Likert scale questionnaire, and seven male teachers participated in semi-structured interviews. The results of this study reveal positive perceptions among teachers about integrating technology into their classrooms. The results indicate that the most effective smart learning tools are learning platforms and that teachers' acquisition of their digital skills reflects positively on their students' digital skills, enabling them to reach higher levels of electronic maturity.